Pengaruh Diabetes Self Management Education (DSME) terhadap kepuasan hidup penderita diabetes melitus tipe II di Puskesmas Kedopok Kecamatan Kedopok Kota Probolinggo - Risky Kusumawardhani; Rizka Yunita; Ana Fitria Nusantara (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Type II DM is a glucose metabolism disorder caused by insulin resistance, insulin secretion which can cause various chronic complications. Diabetes Self Management Education (DSME) facilitates knowledge of self-care skills so that patient can solve the problem. The research aims to determine the effect of Diabetes Self Management Education (DSME) on Life Satisfaction of Diabetics Type II Melitus at the Kedopok Health Center, Kedopok, Probolinggo. The study is pre-experimental, with a one-group pre-post design. Purposive sampling was used to select a population of 69 respondents and a sample of 59 respondents who met the research inclusion requirements. An assessment questionnaire sheet was used as the instrument. The data for the Satisfaction with Life Scale (SWLS) is gathered by editing, coding, scoring, and tabulating. The Wilcoxon signed rank test was used to analyze the obtained data.The results before the DSME was carried was satisfied with 22 respondents (38.6%), after The most DSME carried out were very satisfied 27 respondents (47.4%). The analysis test is found There is The Influence of DSME on Life Satisfaction of Type II Diabetes Mellitus Patients in Kedopok Public Health Center Kedopok Probolinggo with -value 0.000 0.05. Diabetes Self Management Education (DSME) can be used to provide effective education for people with diabetes mellitus because it can improve knowledge, attitudes, and behavior in performing self-care, which aims to support decision- making self-care, problem solving, and life satisfaction